Analisis Strategi Pengembangan Sumber Daya Manusia bagi Pelaku UMKM melalui Program Smexcellence pada Kementerian Usaha Mikro Kecil dan Menengah Republik Indonesia : Studi Kasus Pada Klaster Banten - Jurnal Jurnal; Mukrodi Mukrodi; Umi Rusilowati (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The development of human resources (HR) has become a strategic priority for improving the competitiveness and sustainability of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. To address this challenge, the Ministry of Micro, Small, and Medium Enterprises of the Republic of Indonesia introduced the SMEXcellence Program as a capacity-building initiative through mentoring and collaborative partnerships. This study aims to analyze the human resource development strategy implemented through the SMEXcellence Program, identify the supporting and inhibiting factors influencing its implementation, and examine its impact on strengthening the capacity of MSME actors. This study employed a descriptive qualitative approach. The research was conducted at the Ministry of Micro, Small, and Medium Enterprises of the Republic of Indonesia and the SMEXcellence Banten Cluster. Informants were selected using purposive sampling and consisted of ministry officials, program facilitators, and MSME participants directly involved in the program. Data were collected through in-depth interviews, observations, and document analysis, while data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings indicate that the HR development strategy was implemented through integrated planning, implementation, mentoring, and evaluation stages. The program's effectiveness was supported by institutional commitment, active participation of aggregators, continuous mentoring, and business matching activities. The program significantly improved participants' managerial competencies, business knowledge, innovation capabilities, marketing skills, and overall entrepreneurial capacity.